Improved Photocatalytic Activity of g‐C3N4/ZnO: A PotentialDirect Z‐Scheme Nanocomposite. Issue 38 (13th October 2020) - Ramachandra, Madhushree; Devi Kalathiparambil Rajendra Pai, Sunaja; Resnik Jaleel UC, Jadan; Pinheiro, Dephan
Abstract: In this study, a Z‐scheme g‐C3 N4 /ZnO nanocomposite was synthesized using exfoliation process, which was further characterized using XRD, FT‐IR, UV‐DRS, SEM‐EDAX, PL, EIS, and TGA techniques. The properties of g‐C3 N4 were enhanced when fabricated with ZnO resulting in a better electron mobility, high redox potential, and excellent semiconducting properties. The performance of this heterostructure was evaluated by photocatalytic degradation of malachite green (MG) under visible light irradiation. The g‐C3 N4 /ZnO heterostructure achieved a degradation of 84.3 % within 60 min under visible light irradiation. The degradation reaction follows a pseudo first‐order kinetic model with a reaction rate constant of 0.0329 min −1 . The nanocomposite demonstrated outstanding stability and recyclability. Abstract : g‐C3 N4 /ZnO nanocomposite was synthesized and characterized using various techniques. The synthesized heterostructure showed efficient visible light harvesting and charge separation properties resulting in a high photocatalytic performance for the degradation of organic pollutants from water bodies. The reaction follows a pseudo first‐order kinetics with a Z‐scheme mechanism. These nanocomposites exhibited outstanding stability and reusability.